PENGARUH TEHNIK SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN - Sri Nurhayati (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
This study is trying to find a solution to the problem the researcher found in her preliminary study about reading for understanding. SQ3R is an abbreviation of Survey, Question, Read, Recite dan Review. This technique can increase the students’ involvement on the text they read. This technique also helps to form information in the students’ mind and make it meaningful. This research is a kind of quantitaive research to find the effect of implementation of SQ3R in reading for understanding. The treatment is given after gathering the data that both classes are homogenous. After analyzing the post test result, it can be concluded that there is a significant effect on the implementation of SQ3R on the students’ undertanding. It is supported by the data from the questionannaire which show the students’ respond on the implememtation of SQ3R in reading for understanding an Islamic text written in English.